2016
DOI: 10.1117/1.nph.3.3.031408
|View full text |Cite|
|
Sign up to set email alerts
|

Hemodynamic response to burst-suppressed and discontinuous electroencephalography activity in infants with hypoxic ischemic encephalopathy

Abstract: Abstract. Burst suppression (BS) is an electroencephalographic state associated with a profound inactivation of the brain. BS and pathological discontinuous electroencephalography (EEG) are often observed in term-age infants with neurological injury and can be indicative of a poor outcome and lifelong disability. Little is known about the neurophysiological mechanisms of BS or how the condition relates to the functional state of the neonatal brain. We used simultaneous EEG and diffuse optical tomography (DOT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 51 publications
1
37
0
1
Order By: Relevance
“…6,13,[25][26][27][28][29][30][31] Prior studies in this field have raised the issue related to the cap tolerance by the neonates as a possible factor limiting the duration of DOT data acquisition. Singh et al 6 and Chalia et al 13 adopted a soft and flexible cap (EasyCap, Germany, i.e., our outer layer), with a whole-head coverage for a multimodal DOT-EEG acquisition. Ferradal and colleagues 14 employed a custom-made optode holder, composed of five triangular patches joined together with a neoprene headband, fixed to the head via Velcro straps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,13,[25][26][27][28][29][30][31] Prior studies in this field have raised the issue related to the cap tolerance by the neonates as a possible factor limiting the duration of DOT data acquisition. Singh et al 6 and Chalia et al 13 adopted a soft and flexible cap (EasyCap, Germany, i.e., our outer layer), with a whole-head coverage for a multimodal DOT-EEG acquisition. Ferradal and colleagues 14 employed a custom-made optode holder, composed of five triangular patches joined together with a neoprene headband, fixed to the head via Velcro straps.…”
Section: Discussionmentioning
confidence: 99%
“…Austin et al 32 employed a custom-made helmet with whole-head coverage, made of an outer shell of thermoplastic and an inner part of NIR-absorbing foam. Crucially, in all these DOT studies, the length of registration did not exceeded 2 h, with a minimal length of 60 min 6,14 up to a maximum of 115 min 13 and the gestational age ranged from 34 weeks gestation 13 to term. Here, we showed that the adoption of our hand-made cap (NeoCAP) enabled a safe continuous DOT monitoring for a 7-day period in a very preterm infant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, accurate DOT image reconstruction requires high-quality structural models of the subject's head to act as a prior for image reconstruction. Significant efforts have therefore been made to optimize an age-matched fourdimensional neonatal head model (74) using MRI head atlases as an alternative to subject-specific data (36,49,55). An advantage of using a standard atlas is that it facilitates group comparisons across subjects, as it defines a common coordinate space (75), although this reduces the spatial specificity of the DOT images (76).…”
Section: Structural Priorsmentioning
confidence: 99%
“…On the other hand, the CBF index was higher during wakefulness compared to quiet sleep in preterm infants (Greisen et al, ). A significant hemodynamic response to burst EEG activity (increase in HbO and variable changes in HbR) has been identified in term‐age infants with neurological injury (Chalia et al, ).…”
Section: Introductionmentioning
confidence: 99%